Synthesizing critical discourse analysis with language ideologies: The example of fictional discourse. (June 2018) - Stamou, Anastasia G.
Highlights: Propose a synthesis for the mediation of sociolinguistic diversity in fiction. Bring together the Critical Discourse Analysis with the Language Ideology fields. Underline the role of fictional texts to construct sociolinguistic realities. Abstract: The aim of this paper is to contribute to the emerging discussion about the necessity of getting in dialogue the Critical Discourse Analysis (CDA) with the Language Ideology (LI) fields (Milani and Johnson, 2008). In particular, I attempt to combine a CDA with a LI view, using, as example, the sociolinguistic study of fiction, since it has largely failed to account for the ideological role of fictional discourse to contribute to the shaping of sociolinguistic diversity. Besides, both CDA and LI have much to gain by engaging with each other. On the one hand, CDA might extend its scope of interest, by viewing language not only as a vehicle through which social inequalities are perpetuated, but also as a topic of social inequalities in itself. On the other hand, LI could be enhanced by the methods of closer textual analysis which is characteristic of CDA. Specifically, I draw on the sociocultural CDA approach of Fairclough. Moreover, I exploit both a macro-level approach of language ideologies as widely shared beliefs about language and a micro-level conceptualization of language ideologies as schemata held by speakers to construe the social meaning of particular instances of language use. To illustrate the proposed synthesis, I use one example from representations of youth language in a Greek family sitcom.